Characteristics of gellan gum-LiCF3SO3 polymer electrolytes - Noor, I.S.M.; Majid, Siti Rohana; Arof, Abdul Kariem; Djurado, D.; Neto, S.C.; Pawlicka, A. (Elsevier, 2012)
A new and thermally stable gellan-based polymer electrolytes (PEs) with LiCF3SO3 were prepared and characterized by spectroscopic (FTIR), thermal (TGA, DSC and DMA), structural (X-ray), electrochemical stability (CV. and LSV) and ionic conductivity measurements. The obtained results revealed that the samples are semi-crystalline and are thermally stable up to 234 degrees C. The ionic conductivity measurements revealed that the ionic conductivity of the electrolyte varies with the salt concentration to reach the highest conductivity value of 5.4 x 10(-4) S/cm at room temperature for 40 wt.% of LiCF3SO3. For this compound, when the temperature is raised to 80 degrees C, the ionic conductivity increases to 6.6 x 10(-4) S/cm with an activation energy of 14.6 kJ/mol. Cyclic voltammetry measurements demonstrated that the plating-striping process in highest conducting.gellan-LiCF3SO3 sample occured at 0.55 V and 1.24 V respectively. All results obtained indicate that gellan-based PEs are very promising candidates to be used as electrolytes in Li conducting electrochemical devices. (C) 2012 Elsevier B.V. All rights reserved.